2021
DOI: 10.3389/fenrg.2021.580808
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Ammonia Production Processes

Abstract: Due to the important role of ammonia as a fertilizer in the agricultural industry and its promising prospects as an energy carrier, many studies have recently attempted to find the most environmentally benign, energy efficient, and economically viable production process for ammonia synthesis. The most commonly utilized ammonia production method is the Haber-Bosch process. The downside to this technology is the high greenhouse gas emissions, surpassing 2.16 kgCO2-eq/kg NH3 and high amounts of energy usage of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
174
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(210 citation statements)
references
References 56 publications
(89 reference statements)
0
174
1
2
Order By: Relevance
“…Hence, the production of carbon-neutral synthetic fuels and feedstocks from renewable electricity has been the focus of a growing body of literature. For example, the synthesis of carbon-neutral hydrogen (Borgschulte, 2016), methane (Biswas et al, 2020), methanol (Centi et al, 2020), and ammonia (Ghavam et al, 2021) have all been considered. A number of demonstration projects have been carried out as well (Wulf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the production of carbon-neutral synthetic fuels and feedstocks from renewable electricity has been the focus of a growing body of literature. For example, the synthesis of carbon-neutral hydrogen (Borgschulte, 2016), methane (Biswas et al, 2020), methanol (Centi et al, 2020), and ammonia (Ghavam et al, 2021) have all been considered. A number of demonstration projects have been carried out as well (Wulf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with reviewed studies. Ghavam et al [53] obtained 2.16 t CO 2 -eq/t NH 3 . At the same time, Al-Breiki and Bicer [32] found that ammonia production via steam methane reforming with and without carbon capture and storage (CCS) emits 1.68 and 2.24 t CO 2 -eq/t NH 3 , respectively.…”
Section: Life Cycle Impact Assessment Of Ammonia Productionmentioning
confidence: 96%
“…Ammonia is a corrosive, poisonous and toxic gas with unpleasant smell, which is widely used in various industries including fertilizer, pharmacy and fermentation [ 56 , 57 ]. It may cause burns to the eyes and skin, and respiratory system damage when the concentration is greater than 300 ppm [ 58 ].…”
Section: Health and Medical Monitoringmentioning
confidence: 99%